2017
DOI: 10.1016/j.vetpar.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A candidate gene approach to study nematode resistance traits in naturally infected sheep

Abstract: HighlightsSNPs within genes associated with the development of nematode resistance were sequenced.The SNPs were segregating in two unrelated, domestic and feral, sheep breeds.More samples are required to determine significant associations between SNPs and traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
3
0
5
Order By: Relevance
“…Causal mutant alleles at the DRB1 and DQB2 loci were identified that were associated with this trait. Single nucleotide polymorphisms (SNPs) in three other candidate genes for nematode resistance and body weight were examined in populations of domestic Scottish Blackface and free-living Soay ewe lambs, and a nominally significant association between an IL23R SNP and body weight was found [58].…”
Section: Genetic Diversity Qtl and Candidate Gene Characterizationmentioning
confidence: 99%
“…Causal mutant alleles at the DRB1 and DQB2 loci were identified that were associated with this trait. Single nucleotide polymorphisms (SNPs) in three other candidate genes for nematode resistance and body weight were examined in populations of domestic Scottish Blackface and free-living Soay ewe lambs, and a nominally significant association between an IL23R SNP and body weight was found [58].…”
Section: Genetic Diversity Qtl and Candidate Gene Characterizationmentioning
confidence: 99%
“…The extensive work on phenotypes and associated parasitism rates has allowed the Soay sheep system to be explored with candidate gene approaches (Brown et al 2013) to identify genes related to parasite resistance (Wilkie et al 2017). Soay sheep have also been studied to determine whether parasitism impacts diet selection for application to farmed breeds (Jones et al 2006).…”
Section: <Comp: Please Insert Figure 2 Here>mentioning
confidence: 99%
“…Como alternativa al uso de medicamentos, para el control de los PGI se ha sugerido la selección de animales genéticamente resistentes (6,13,14). Este proceso de cría selectiva para la resistencia al PGI utiliza el recuento de huevos fecales (FEC), ensayos de anticuerpos, volumen de células empaquetadas y puntuación de anemia por el método FAMACHA ® , como indicadores de resistencia (7,15).…”
Section: Introductionunclassified
“…En razón a lo anterior, los estudios de asociación de genoma completo en diversas razas ovinas han asociado determinados polimorfismos en los genes GLI1 y IL20RA como candidatos a la resistencia contra PGI (13,14,15,19). Dichos polimorfismos no han sido caracterizados en la raza OPC.…”
Section: Introductionunclassified